Aspectos jurídicos da inteligência competitiva - Coxe, Rodrigo Antonio Garcia (2018)
The incessant search for competitiveness, due to the factors related to economic globalization, required companies to know the environment in which they operate, in order to make strategic decisions possible. The emergence of new technologies and ease of access to information have further boosted this process. As a result, companies began to seek data from various sources on the performance of their competitors, including information on products, processes and markets. However, companies are not always aware of the legal implications that can affect this process and therefore some studies mention the need to be attentive to these aspects, being that of these, few explicitly in the legal scope, what are the issues that must be punctually considered in the process of applying Competitive Intelligence (CI) and its activities. This research uses the Cycle of CI elaborated through the Manual of IC of 2004, elaborated by the team of the Nucleus of Technological Information in Materials - NIT / Materials of the UFSCar. Thus, this study verified whether the systematic process involved in the CI cycle is in accordance with what determines the legal order. Thus, specific objectives include: investigating, from a bibliographic and documentary survey, the legal aspects of HF and analyzing each of the activities involved in the phases of HF cycle under this same perspective. Methodologically, the research is classified as theoretical and qualitative, adopting an interdisciplinary approach, and based on a bibliographic review of the themes involved, which will facilitate the study of legal aspects related to HF. Legal aspects focused on all phases of the ICC, as well as on all related activities, and their non-observance showed the existence of legal, administrative, civil and criminal implications that could harm the activity. On the other hand, technical compliance with the same legal aspects brings a framework of the activity to the current legislation, and it is even possible for a legal professional to become the team responsible for the CI activity, ensuring even more that this activity is aligned ethical, legal and legal rules.